Determinants of E-WOM and Intention to Revisit Beach in Yogyakarta Indonesia Post-pandemic Through Visitor Satisfaction - Apriani, Ari; Meliantari, Dian; Desty Febrian, Wenny; Herawati, Yanthy; ., Windayanti (KnE Social Sciences, 2023)
Efforts to promote beach destinations through online media certainly encourage many tourists to visit currently viral destinations on social media. This study aims to determine the determinants of E-WOM and intention to return to the beach in Yogyakarta through visitor satisfaction. This study included 200 respondents who were all tourists in Jakarta and Yogyakarta, and who had visited the beach in Yogyakarta. This study will develop and add other constructs/variables that can be predictors of visitor behavior to make a return visit to a tourist attraction, from previous research that has been done. The method used in this research is quantitative analysis with SEM analysis tools and SmartPLS 3.3 tools. This research is expected to be an improvement for beach tourism managers in Yogyakarta to improve their tourism objectives so that visitors who have visited the beach in Yogyakarta have an interesting impression so as to increase interest in visiting again Keywords: destination accessibility, destination attraction, destination image, electronic word of mouth, intention to revisit, post-pandemic, visitor satisfaction